If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 2) + -3(x + -1) = 19 Reorder the terms: 7(2 + x) + -3(x + -1) = 19 (2 * 7 + x * 7) + -3(x + -1) = 19 (14 + 7x) + -3(x + -1) = 19 Reorder the terms: 14 + 7x + -3(-1 + x) = 19 14 + 7x + (-1 * -3 + x * -3) = 19 14 + 7x + (3 + -3x) = 19 Reorder the terms: 14 + 3 + 7x + -3x = 19 Combine like terms: 14 + 3 = 17 17 + 7x + -3x = 19 Combine like terms: 7x + -3x = 4x 17 + 4x = 19 Solving 17 + 4x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 4x = 19 + -17 Combine like terms: 17 + -17 = 0 0 + 4x = 19 + -17 4x = 19 + -17 Combine like terms: 19 + -17 = 2 4x = 2 Divide each side by '4'. x = 0.5 Simplifying x = 0.5
| 8z=-48 | | y=5/14x-15/4 | | 2-5x=4x-10x | | -2(4,7)= | | 12x^2-2=14 | | -10+5x=25 | | 8x+4-2x+8= | | x=16.25x-5 | | 5x=16.25x | | 49x^2+15=56x | | 5x=16.25 | | ((x^2-36)/(2x-2))/((x^2+12x+36)/(x^2+5x-6)) | | 9x+6=57 | | 5(11x+5)+32+9x= | | -3x-7=1 | | ((y^2-1)/(y-1))/((y+1)/(2y-2)) | | -6=x-2 | | 6y-x=6 | | -70=2x+10 | | ((x^2-81)/(x))/((x+9)/(x-9)) | | 23m+5-7m=4m-19 | | -3(5p+4)-2(3-14p)=3(7+4p) | | ((x+3)/(7))/((4x+12)/(5)) | | -7x=-2x-25 | | -50=20x+10 | | ((x^2+10x+25)/(x^3+125))*((2)/(x+5)) | | -8-x-3=2 | | ((y^3+343)/(y^2-49))*((y-7)/(4y)) | | 0-(-2)= | | 6x-7y=-98 | | 0.4=x/7 | | 4x-2y=-44 |